More Rhythmic Interactions in Two (or Three) Aksak Performances - Fernando Benadon (Empirical Musicology Review, 2016)
Goldberg (this issue) presents evidence of interactions between percussive timing and song structure in two 3+2+2-meter Balkan performances. Using interonset measurements and checking carefully for statistical significance, he shows that formal and contextual characteristics of each performance coincide with timing changes at the level of the beat and bar, with durations becoming slightly shorter or longer at consistent locations. I review Goldberg’s main findings and contribute brief supporting analyses. For one of the songs, I provide additional context regarding verse meter, melodic structure, anacrustic drive, links between timing and breathing, and offsets between taps and syllabic onsets. For the other song, I attempt to tease out the difference between shortened non-isochronous beats (an altered aksak ratio) and shortened bars (an accelerated tempo). I end with a brief analysis of a different song by the same performer as the first song, showing that the timing effects Goldberg observed in one are also present in the other.